1980
DOI: 10.1128/jb.144.3.869-876.1980
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and repression of homocitrate synthase by lysine in Penicillium chrysogenum

Abstract: Homocitrate synthase in the first enzyme of the lysine biosynthetic pathway. It is feedback regulated by L-lysine. Lysine decreases the biosynthesis of penicillin (determined by the incorporation of [14C]valine into penicillin) by inhibiting and repressing homocitrate synthase, thereby depriving the cell of alpha-aminoadipic acid, a precursor of penicillin. Lysine feedback inhibited in vivo the biosynthesis and excretion of homocitrate by a lysine auxotroph, L2, blocked in the lysine pathway after homocitrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 19 publications
(16 reference statements)
2
15
0
2
Order By: Relevance
“…We found that emetic toxin production was sharply decreased in the media supplemented with a high concentration of leucine, isoleucine or glutamic acid. This finding is similar to previous observations that the production of a botulinum neurotoxin was suppressed by high levels of certain amino acids (8,10), and that the biosynthesis of antibiotic penicillin was negatively regulated by several amino acids (3,7).…”
Section: Discussionsupporting
confidence: 92%
“…We found that emetic toxin production was sharply decreased in the media supplemented with a high concentration of leucine, isoleucine or glutamic acid. This finding is similar to previous observations that the production of a botulinum neurotoxin was suppressed by high levels of certain amino acids (8,10), and that the biosynthesis of antibiotic penicillin was negatively regulated by several amino acids (3,7).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this assumption was the notion that in P. chrysogenum, one target for lysine regulation is homocitrate synthase, which catalyzes the initial reaction of lysine biosynthesis. Lysine was found to cause both feedback inhibition of homocitrate synthase activity and repression of its synthesis (14,26). In agreement with these findings, it was shown that the AA pool available for penicillin production was reduced in lysine-grown mycelia (23,38).…”
supporting
confidence: 60%
“…When the binding ['4C]NeuAc to proteins was analysed, reaction mixtures were precipitated with 10 % (w/v) trichloroacetic acid as described by Luengo et al (1980). The trichloroacetic acid solution was cooled to 0°C for 10 min and centrifuged at 5000 g for 5 min.…”
Section: Sialyltransferase Activitymentioning
confidence: 99%